DANA DARURAT DI MASA PANDEMI COVID-19 - Kumajas, Lydia Ivana; Wuryaningrat, Nikolas Fajar (Modus, 2021)
ABSTRACTIn financial management, the main issue in financial planning is estimating future cash flows, because it is influenced by various risks. One way to reduce risk is by placing an emergency fund. During the Covid-19 pandemic, the importance of financial planning was seen by placing an emergency fund when individuals, families, and companies experienced economic problems due to the Covid-19 pandemic. This study aims to describe the communities’ awareness and knowledge and their readiness to face ‘rainy day’ by preparing financial umbrella or emergency fund, and whether the greater the income, the greater the umbrella allocated as stated in Keynes's theory. Descriptive research methods are used to get this picture. Online survey with Survey Monkey application was conducted on a small portion of the community in various regions in Indonesia. The results of this study showed that 91 community members were aware of emergency fund, although not all of them prepared it. The interesting finding is that high-income respondents were not of the group which allocated bigger emergency fund. Hence, this could not give fit descriptions with Keynes Theory.        Keywords: Pandemic of Covid-19; rainy day; Keynes theory; emergency fund ABSTRAKDalam manajemen keuangan, kesulitan utama dalam membuat perencanaan adalah mengestimasi arus kas di masa depan, karena dipengaruhi oleh berbagai risiko. Salah satu cara untuk mengurangi risiko adalah membuat perencanaan keuangan dengan menempatkan dana darurat. Di masa pandemi Covid-19 ini terlihat pentingnya perencanaan keuangan dengan menempatkan dana darurat atau ketika individu/perusahaan mengalami masalah ekonomi akibat pandemi Covid-19. Penelitian ini bertujuan mendapatkan gambaran kesadaran dan pengetahuan masyarakat dan kesiapannya menghadapi keadaan sulit ‘rainy day’ dengan menyiapkan dana darurat sebagai payung keuangan, dan apakah semakin besar penghasilan maka akan semakin besar dana darurat yang dialokasikan seperti yang dikemukakan dalam teori Keynes. Metode penelitian deskriptif digunakan untuk mendapatkan gambaran tersebut. Survei online dengan aplikasi Survey Monkey dilakukan pada sebagian kecil masyarakat di berbagai daerah di Indonesia. Hasil penelitian dari 91 responden sebagian besar sudah mengetahui mengenai dana darurat, akan tetapi walaupun mengetahui pentingnya dana darurat tidak semua sudah menyediakan dana tersebut. Menariknya, responden pada kelompok penghasilan tertinggi bukanlah kelompok yang mengalokasikan dana darurat paling besar. Dengan demikian, tidak terlalu memberikan gambaran yang sesuai dengan teori Keynes.Kata kunci: Pandemi Covid-19; risiko; teori Keynes; dana darurat